2022
DOI: 10.1158/2159-8290.cd-22-0220
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastasis Initiation Is Coupled with Bone Remodeling through Osteogenic Differentiation of NG2+ Cells

Abstract: The bone microenvironment is dynamic and undergoes remodeling in normal and pathological conditions. Whether such remodeling impacts disseminated tumor cells and bone metastasis remains poorly understood. Here, we demonstrated that pathological fractures increase metastatic colonization around the injury. NG2+ cells are a common participant of bone metastasis initiation and bone remodeling in both homeostatic and fractured conditions. NG2+ bone mesenchymal stromal cells (BMSCs) often co-localize with DTCs in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The frequency of each cell type among biotin+ cells was normalized to that among biotin-cells to deduce enrichment or depletion in the metastatic niche. In all four models, we observed a consistent enrichment of endothelial cells and osteoblasts/osteoprogenitor cells ( Figure 1I ), which is consistent with previous discoveries of roles of perivascular niches 13 , osteogenic niches 57,22 , and skeletal stem cells 23 . In addition, we also noticed unbalanced distribution of monocytes, macrophages, and T cells between biotin+ vs. biotin-populations.…”
Section: Resultssupporting
confidence: 91%
“…The frequency of each cell type among biotin+ cells was normalized to that among biotin-cells to deduce enrichment or depletion in the metastatic niche. In all four models, we observed a consistent enrichment of endothelial cells and osteoblasts/osteoprogenitor cells ( Figure 1I ), which is consistent with previous discoveries of roles of perivascular niches 13 , osteogenic niches 57,22 , and skeletal stem cells 23 . In addition, we also noticed unbalanced distribution of monocytes, macrophages, and T cells between biotin+ vs. biotin-populations.…”
Section: Resultssupporting
confidence: 91%
“…With its long period of metastatic latency, the bone represents a typical metastatic site permissive for dormancy and many bone cells such as stromal, vascular cells as well as osteoclasts can actively support dormancy [9][10][11] . Current evidence suggests that tissue perturbations in the bone environment such as traumatic injury leading to osteogenic repair, can cause outgrowth of metastatic dormant cells 22 . However, the changes in the bone leading to spontaneous metastatic relapse after a long period of time are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, systemic inflammatory cell mobilization in the lung environment caused by surgery was also reported to induce the reactivation of dormant cells 21 . Specifically in the bone, pathogenic fractures and the associated osteogenic repair response were shown to induce the outgrowth of bone DTCs 22 .…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, tumor cells interact with various cells in the bone microenvironment, such as bone marrow stromal cells (BMSCs), osteoclast (OCs), osteoblasts (OBs), endothelial cells (ECs), BMAs, immune cells, etc., causing adaptive changes in the bone marrow microenvironment and providing favorable conditions for tumor cell invasion and growth ( 12 ). For instance, in vivo studies have found that BMSCs can be chemotactically guided to tumor cells, participating in the construction of the tumor microenvironment ( 13 ). Lung cancer cells can also activate OCs, causing bone matrix dissolution and creating conditions for their adhesion and settlement ( 14 ).…”
Section: The Role Of the Bone Marrow Microenvironment In Lung Cancer ...mentioning
confidence: 99%